2022
DOI: 10.9734/ijecc/2022/v12i1030868
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Extent of Adoption of Agro- Enterprises by Women Agripreneurs and Constraints Faced Due to the Climatic Severity in Coastal Odisha, India

Abstract: Women agripreneurship development became an essential part of human resource development. It makes the women financially independent and enhances the self esteem of them. The present study has been conducted with the objective to know the extent of adoption of agricultural enterprises by women agripreneurs of Coastal Odisha and it also determine climatic constraints. The study has been conducted in two districts of Odisha that are Balasore and Jagatsinghpur. Total 210 women agripreneurs were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Among the weather-related problems, the problem of floods, irregular monsoons, unseasonal rains and gale winds were reported by respondents. Nayak et al [12] also reported floods and cyclones as the main constraints for agro-enterprises in the coastal region. In pests & diseases, cashew stem and root borer, tea mosquito bug in cashew; wilt in black pepper; mites, rhinoceros beetle & rugose white fly in coconut; koleroga and yellow leaf disease in arecanut; fruit fly in mango; viral diseases in papaya and okra were reported.…”
Section: Problems Faced By Coastal Farmers In Agriculture and Horticu...mentioning
confidence: 99%
“…Among the weather-related problems, the problem of floods, irregular monsoons, unseasonal rains and gale winds were reported by respondents. Nayak et al [12] also reported floods and cyclones as the main constraints for agro-enterprises in the coastal region. In pests & diseases, cashew stem and root borer, tea mosquito bug in cashew; wilt in black pepper; mites, rhinoceros beetle & rugose white fly in coconut; koleroga and yellow leaf disease in arecanut; fruit fly in mango; viral diseases in papaya and okra were reported.…”
Section: Problems Faced By Coastal Farmers In Agriculture and Horticu...mentioning
confidence: 99%